Correction: Risk factors for drug-related problems in a general hospital: A large prospective cohort. - Valdjane Saldanha; Ivonete Batista de Araújo; Sara Iasmin Vieira Cunha Lima; Rand Randall Martins; Antonio Gouveia Oliveira (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0230215.].